Emotional Intelligence Educational Card Game to Prevent Verbal Abuse at Elementary Schools in Southeast Pontianak - Nur Kur'ani; Rini Elvri (Universitas PGRI Yogyakarta, 2026)
Cases of verbal abuse in schools are often considered normal. For example, rude words to friends, such as saying “anjay